Preparation For Knowledge Management Implementation: A Nemisa Case Study - Mongalo, Sefura Sandra (2007)
This report is an evaluative study conducted to determine NEMISA's readiness to implement knowledge management. The report defines knowledge management (KM) and knowledge to put these two concepts in perspective and it also elaborates on factors which have to be taken into account when an organization introduces KM.